Running for an academic degree: ultra-Orthodox women studying physical education at a non-religious college. Issue 8 (13th October 2022) - Avugos, Simcha; Zach, Sima
ABSTRACT: The continuous trend of ultra-Orthodox ('Haredi') women enrolling in higher education institutions has not been widely investigated. The current study explored their reasons for pursuing an academic degree, their radical choice of physical education (PE) as a career, as well as their experiences and reflections on this process. Eighteen Israeli ultra-Orthodox female students aged 21–41 participated in the study. A mixed-methods convergent design approach was used for data collection. Religious affiliation and its intersection with social class were used as a theoretical framework for the interpretation of the findings. The analysis of the written data from the questionnaires and the focus group interviews showed that economic considerations dominated their motivations to attend college. Almost all of these women plan to use their studies in PE to improve their earning capacity. A passion for sports from an early age was their main reason for selecting this particular degree. Among the difficulties they faced were the heavy academic workload, as well as knowledge gaps due to their insufficient educational background. The women expressed varying attitudes toward openness to the secular society – mainly in reference to the younger generation, in light of the changes that their highly conservative community is presently undergoing. Future directions for research and educational policy are presented and discussed.